Introduction to Environmental Engineering - Vesilind, P. Aarne (Thomson/Brook/Cole, 2004)
This text has two unifying themes: materials balances and environmental ethics. The authors demonstrate that environmental problems need to be solved using a holistic approach and incorporate ethical decision-making into the discussions and problems.